BURIALS OF THE EARLY MIDDLE BRONZE AGE MOUND I OF THE GUDERMES MOUNDS I - Malasev, Vladimir Ur'evic; Ataev, Gamzat Dibirovic; Sajpudinov, Murad Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2023)
The excavation in 2017 of the burial Mound I of the Gudermes mounds I revealed three distinct burial groups from different time periods, the oldest of which is associated with the Maikop culture. Our paper primarily focuses on intrusive burials from the early stage of the Middle Bronze Age, encompassing two subgroups with distinct funerary rituals. The skeletons in the first subgroup (Burials 9, 10, 13, and possibly 3) were laid in a semi-flexed position on the left side, with the head oriented to the ENE. Burial 3, situated in the mound’s center, was constructed in a rectangular pit with walls lined using a mosaic of irregular stones and cobblestones. The grave was covered with logs, topped by a layer of river pebbles. Surrounding this central burial were three contemporaneous burials of a man, a woman, and a child. The accompanying grave goods comprised a stone axe, a bronze dagger-knife, and six bone hammer-head pins. Another subgroup comprises two supine burials wherein skeletons were laid on their backs, with their heads facing the SSE. Based on stratigraphic data, these burials are relatively recent. In terms of funerary ritual and inventory details, they align with the initial period of the Middle Bronze Age and are similar to the first group. The inventory includes fragments of vessels, a bronze trapezoidal pendant, a pierced bronze spiral piece, and a fragment of a bronze object (possibly a bead), along with glass beads. Examination of funerary rituals and inventory facilitates the identification of parallels with Middle Bronze Age sites of Chechnya, Ingushetia, the Central Caucasus, and the Kuban region, allowing us to attribute the early burials of Mound I at the Gudermes mounds I to the North Caucasian culture.